Central core disease--a case report. - Myong, N. H. (Korean Academy of Medical Sciences, 1993)
Central core disease is a rare congenital myopathy characterized by the formation of "cores" that consist of abnormal arrangement of myofibrils inside the myofibers. We report a 5-year-old Korean girl who showed a fairly typical clinical course of non-progressive muscle weakness. Electrodiagnostic studies showed low-amplitude polyphasic electromyograph and normal nerve conduction velocity. Gastrocnemius muscle biopsy showed central cores in over 80% of the fibers on H&E section. Histochemistry revealed deficient or absent mitochondrial enzyme in the cores and type I predominance. Ultrastructurally both structured and non-structured cores were found separately or simultaneously in one fiber. This case is the first report in the Korean literature.